Building Ho's army Chinese military assistance to North Vietnam - Li, Xiaobing 1954- (University Press of Kentucky, 2019)
"The Chinese have a decades long history of aiding the Vietnamese through military training, strategic advising, and monetary means. As a communist state bordering Vietnam, China actively supported Ho Chi Minh's wars against France from 1950 - 1954 and against America from 1965 - 1970. Even after the signing of the Geneva Peace Agreement, China continued its military assistance to North Vietnam. Between 1955 and 1963, Chinese military aid to Ho totaled $106 million, including weapons and ammunition that armed more than one hundred infantry battalions, or about 80,000 men. The massive contributions to North Vietnam enabled Ho to build up a strong conventional force. After 1964, China increased its aid, and from 1964 to 1973, it provided approximately $20 billion more in military and economic aid to Vietnam. Among the Communist states, China was the largest supplier of war materials to North Vietnam until 1967, supplying about 44.8 percent of total military aid that year. In Building Ho's Army: Chinese Military Assistance to North Vietnam, Xiaobing Li assembles a detailed overview of Chinese military aid, training, and cooperation with the North Vietnamese Army (NVA) in the 1950s and 60s. Western strategists and historians have long speculated about Chinese military assistance in the Vietnam War, but it was not until recently that newly available archival materials revealed the true extent of Chinese involvement. Li uses these new Communist sources in an unprecedented manner to offer a Chinese military perspective on the Vietnam War. This book builds upon previous scholarly efforts to add a better understanding of the ground-level contribution of China's effort to improve NVA combat effectiveness in the Vietnam War."
Keywords: Geschichte 1950-1969; Militärhilfe; Militärische Kooperation; Nordvietnam; China; Vietnam / Quân đội nhân dân / History; Military assistance, Chinese / Vietnam (Democratic Republic); Vietnam (Democratic Republic) / Military relations / China; China / Military relations / Vietnam (Democratic Republic); Vietnam (Democratic Republic) / History, Military; Vietnam / Quân đội nhân dân; Military assistance, Chinese; Military relations; Vietnam (Democratic Republic); History; Military history